Peripheral loss of CD8+CD161++TCRVα7·2+ mucosal‐associated invariant T cells in chronic hepatitis C virus‐infected patients. (5th January 2016) - Barathan, Muttiah; Mohamed, Rosmawati; Vadivelu, Jamuna; Chang, Li Y.; Saeidi, Alireza; Yong, Yean K.; Ravishankar Ram, M.; Gopal, Kaliappan; Velu, Vijayakumar; Larsson, Marie; Shankar, Esaki M.
Abstract: Background: Mucosal‐associated invariant T (MAIT) cells play an important role in innate host defence. MAIT cells appear to undergo exhaustion and are functionally weakened in chronic viral infections. However, their role in chronic hepatitis C virus (HCV) infection remains unclear. Materials and methods: We investigated the frequency of CD8 + CD161 ++ TCR Vα7.2 + MAIT cells in a cross‐sectional cohort of chronic HCV‐infected patients ( n = 25) and healthy controls ( n = 25). Peripheral blood mononuclear cells were investigated for circulating MAIT cell frequency, liver‐homing (CCR5 and CD103), biomarkers of immune exhaustion (PD‐1, TIM‐3 and CTLA‐4), chronic immune activation (CD38 and HLA‐DR), and immunosenescence (CD57) by flow cytometry. Results: The frequency of MAIT cells was significantly decreased, and increased signs of immune exhaustion and chronic immune activation were clearly evident on MAIT cells of HCV‐infected patients. Decrease of CCR5 on circulating MAIT cells is suggestive of their peripheral loss in chronic HCV‐infected patients. MAIT cells also showed significantly increased levels of HLA‐DR, CD38, PD‐1, TIM‐3 and CTLA‐4, besides CD57 in chronic HCV disease. Conclusions: Immune exhaustion and senescence of CD8 + CD161 ++ TCR Vα7.2 + MAIT cells could contribute to diminished innate defence attributes likely facilitating viral persistence and HCV disease progression.